Arab Students' Writing in English at the College Level : Challenges and Remedies - Rass, Ruwaida Abu, (Critical New Literacies: The Praxis of English Language Teaching and Learning ;, 2025)
This book contains detailed theoretical information as well as practical strategies, techniques and pedagogical tips. It also includes analysis to the problems and challenges that face ESL/EFL students in general and Arab learners in specific. The book could be of interest not only to EFL researchers in academic writing, writing instructors, EFL educators at the college level, policymakers, and undergraduate and graduate students, but also for any second or foreign language teachers.